استخدامات الصحفيين السودانيين لتقنيات الذكاء الاصطناعي في العمل الصحفي - عوض الكريم عبد الماجد, أيمن هاشم (Gezira Journal of Educational Sciences and Humanities; مجلد 21 عدد 2 (2024), 2026)
هدفت الدراسة إلى تسليط الضوء على استخدامات الصحفيين السودانيين للذكاء الاصطناعي في العمل الصحفي، الذي يُعتبر من أهم وأحدث التقنيات التكنولوجية الحديثة، حيث يُحظى باهتمام كبير في المؤسسات الصحفية لما يقدمه من خدمات من حيث إنشاء المحتوى والوصول إلى المعلومات وتقليل الجهد وتسهيل البحث عن البيانات ومعالجتها باستخدام الذكاء الاصطناعي الذي يلعب دوراً كبيرا ومهماً في تحسين الجودة وزيادة قدرات العمل الصحفي بكفاءة وتحسين الإنتاجية. تم إجراء الدراسة الميدانية باستخدام الاستبانة والمقابلة بوصفها أدوات لجمع البيانات بالإضافة إلى الملاحظة بالمشاركة، حيث لخصّت الدراسة عدد من النتائج، أهمها: أظهرت نتائج الدراسة وجود علاقة ارتباطية موجبة قوية ذات دلالة إحصائية بين استخدام الذكاء الاصطناعي وجودة المحتوى الصحفي، أن أغلب أفراد العينة أتفقوا على أن المؤسسات الصحفية والصحفيين السودانيين يستخدمون تقنيات الذكاء الاصطناعي في العمل الصحفي إلى حد كبير، أن أغلب أفراد العينة يعتمدون على برامج وتطبيقات الذكاء الاصـــطناعي في العمــــــل الصحــــــــفي وأهمها Chat GPT ,In Shot, Cap Cut، كما أن المبحوثين اتفقوا على أن تقنيات الذكاء الاصطناعي ساهمت بشكل كبير في تحسين جودة العمل الصحفي وتسهيله على الصحفيين، إلا أن هنالك بعض المهام الصحفية التي لايمكن الاستعاضة عنها بالذكاء الاصطناعي وتطبيقاته، لأنّها تعتمد على حضور الصحفي ومشاعره وانفعالاته وتفاعله مع الجمهور. تُوصي الدراسة بضرورة تدريب وتأهيل الصحفيين السودانيين مع استقطاب الخبراء والمتخصصين في مجال تقنيات الذكاء الاصطناعي وهذا بهدف الاسهام في نجاح العمل الصحفي. ومواكبة ومسايرة التطورات الحادثة في مجال استخدامات تقنيات الذكاء الاصطناعي في العمل الصحفي والاطلاع على كل ما هو جديد ومتطور بمختلف الوسائل والتطبيقات التقنية. This study aimed to shed light on the use of artificial intelligence (AI) technologies by Sudanese journalists in journalistic practice. AI is considered one of the most significant and recent technological innovations and has attracted considerable attention within media organizations due to the services it provides in content generation, information retrieval, effort reduction, and the facilitation of data search and processing. AI plays a vital role in enhancing quality, increasing the efficiency of journalistic work, and improving productivity.The field study employed a questionnaire and interviews as the primary data collection tools, in addition to participant observation. The findings revealed a strong, positive, and statistically significant correlation between the use of AI and the quality of journalistic content. Most respondents agreed that Sudanese media institutions and journalists make extensive use of AI technologies in journalistic work. The majority also reported relying on AI-based programs and applications, particularly ChatGPT, InShot, and CapCut. Furthermore, respondents concurred that AI technologies have substantially improved the quality of journalistic work and facilitated journalists’ tasks. Nevertheless, certain journalistic functions cannot be replaced by AI applications, as they depend on the journalist’s physical presence, emotions, and interaction with the audience. The study recommends the training and qualification of Sudanese journalists and the engagement of experts and specialists in AI technologies to enhance the success of journalistic practice. It also emphasizes the importance of keeping pace with ongoing developments in AI applications in journalism and staying informed about emerging tools and technological innovations.